Soybean responses to foliar amino acid application and high plant densities - Calero-Hurtado, Alexander; Pérez-Díaz, Yanery; Peña-Calzada, Kolima; Jiménez-Medina, Alay; Kukurtcu, Bulent (Revista de Ciencias Agrícolas, 2025)
The combination of plant densities and foliar application of amino acids may be a viable strategy to increase sustainable soybean crop production. Therefore, the objective of this study was to evaluate the effects of high plant densities and the foliar application of amino acids (VIUSID® Agro) on the growth and yield of soybeans [Glycine max (L.) Merr] in the rainy season. This research was conducted from May to September 2023, with treatments arranged in split plots, randomized blocks, and replicated three times. The main plots corresponded to the two plant densities (PD) (300,000 and 500,000 ha⁻¹), and the secondary plots were defined by the foliar application of amino acids (AA)—non-AA (A0), 0.25 L ha⁻¹ (A1), and 0.50 L ha⁻¹ (A2)—to improve soybean growth and yield responses. The results showed that plant densities increased growth indicators, with the most significant increase was observed at a density of 300,000 plants ha-1. In contrast, production parameters and yield were higher at a density of 500,000 plants ha-1. However, the 0.25 L ha⁻¹ treatment showed superior effects on growth at the density of 300,000 plants ha⁻¹, while yield and yield components were higher at the 0.5 L ha⁻¹ treatment. Additionally, at a density of 500,000 plants ha⁻¹, the 0.5 L ha⁻¹ treatment stimulated the growth of soybean plants, while the 0.25 L ha⁻¹ treatment exhibited higher yields.